Broad Neutralizing Activity Against Ebolaviruses Lacking the Mucin-Like Domain in Convalescent Plasma Specimens From Patients With Ebola Virus Disease. (25th June 2018) - Luczkowiak, Joanna; Lasala, Fatima; Mora-Rillo, Marta; Arribas, Jose R; Delgado, Rafael
Abstract: Background: In Ebola virus (EBOV) infection, the specific neutralizing activity of convalescent plasma against other members of the Ebolavirus genus has not been extensively analyzed. Methods: We measured the neutralizing activity in plasma from 3 survivors of the recent outbreak due to the Makona variant of EBOV and tested its neutralizing potency against other variants of EBOV (ie, Mayinga and Kikwit) and against Sudan virus (SUDV), Bundibugyo virus (BDBV), and Reston virus (RESTV), using a glycoprotein (GP)–pseudotyped lentiviral system both with full-length GP and in vitro–cleaved GP (GPCL ). Results: Convalescent plasma specimens from survivors of EBOV infection showed low neutralizing activity against full-length GPs of SUDV, BDBV, RESTV, and EBOV variants Mayinga and Kikwit. However, broad and potent neutralizing activity was observed against the GPCL forms of SUDV, BDBV, and RESTV. Discussion: Removal of the mucin-like domain and glycan cap from the GP of members of the Ebolavirus genus presumably exposes conserved epitopes in or in the vicinity of the receptor binding site and internal fusion loop that are readily amenable to neutralization. These types of broad neutralizing antibodies could be induced by using immunogens mimicking GPCL .